2018
DOI: 10.1002/pssb.201800119
|View full text |Cite
|
Sign up to set email alerts
|

Localized Photoluminescence Imaging of Bi‐Layered Cuprous/Cupric Oxide Semiconductor Films by Synchrotron Radiation

Abstract: To develop multi‐layered semiconductor film devices, like a solar cell device, effects of localized impurities and layered interface mismatches on photovoltaic properties should be understood quantitatively and controlled effectively. However, the research of localized photoluminescence on layered semiconductor film devices is delayed. This is because, unfortunately, a measurement method for photoluminescence properties with spatial resolution on the sub‐micron scale, which could provide much of the local phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 52 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…The obtained peaks in Figure 4 are related to the emission light energies reported for each material constituting the film sample. It was noted that the intensity of light emission was weak compared to the previous work [ 12 ], due to a smaller-sized X-ray beam. Nonetheless, despite reducing the X-ray beam’s size, the local measurement of photoluminescence spectra was successful, although a delicate set-up for the spectrometer was necessary.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…The obtained peaks in Figure 4 are related to the emission light energies reported for each material constituting the film sample. It was noted that the intensity of light emission was weak compared to the previous work [ 12 ], due to a smaller-sized X-ray beam. Nonetheless, despite reducing the X-ray beam’s size, the local measurement of photoluminescence spectra was successful, although a delicate set-up for the spectrometer was necessary.…”
Section: Resultsmentioning
confidence: 63%
“…It was also reported that the (0001)-oriented ZnO layer emits not only near-band emissions at 3.25 eV –3.3 eV by recombination [ 35 ], but also visible light emissions at 2.28 eV and 2.8 eV [ 36 ]. In addition, the substrates possess emission peaks at 1.9 eV and 2.7 eV [ 12 ]. The obtained peaks in Figure 4 are related to the emission light energies reported for each material constituting the film sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations